Pengaruh Penggunaan Media Pembelajaran Storyboard terhadap Hasil Belajar Siswa pada Mata Pelajaran SKI di MTsN 1 Medan - Khairul Anwar; Afrahul Fadhila Daulai (At Turots: Jurnal Pendidikan Islam, 2023)
The aim of this research is to determine the effect of using storyboard learning media on student learning outcomes in SKI lessons at MTsN 1 Medan. This research uses quantitative methods, quasi-experimental techniques and the design used is a non-equivalent control group. The research population consisted of all grade VIII students at MTsN 1 Medan, totaling 343 students. The sample was selected using a purposive technique. Class VII-D was chosen as the experimental class, while class VIII-E was chosen as the control class, with each class having 30 students. Test instruments and questionnaires were chosen by researchers to collect data, which was then analyzed using parametric statistical analysis techniques. The results of the research show that the use of storyboard learning media significantly influences student learning progress in SKI subjects at MTsN 1 Medan. This is supported by the results of the hypothesis test, where the value of tcount (6.120) exceed ttable (2.002), so that H0 is rejected and Ha is accepted. Thus, it can be concluded that the use of storyboard media has a significant effect on student learning outcomes in SKI subjects at MTsN 1 Medan.